2020
DOI: 10.3758/s13414-019-01915-0
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic and triadic search: Benefits, costs, and predictors of group performance

Abstract: In daily life, humans often perform visual tasks, such as solving puzzles or searching for a friend in a crowd. Performing these visual searches jointly with a partner can be beneficial: The two task partners can devise effective division of labour strategies and thereby outperform individuals who search alone. To date, it is unknown whether these group benefits scale up to triads or whether the cost of coordinating with others offsets any potential benefit for group sizes above two. To address this question, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 28 publications
(61 reference statements)
2
20
0
2
Order By: Relevance
“…As in previous studies (Wahn et al, 2017; Wahn et al, 2020); our reasoning is that if dyads exceed this simulated joint performance, then they attained their higher joint performance by successfully collaborating in the tracking task (i.e., a division a labor division strategy). To differentiate this type of benefit from the collective benefit, and to denote that a collaboration between coactors is required, we henceforth refer to it as a “collaborative benefit” (for a more in-depth discussion of different types of group benefit criteria, see Wahn, Kingstone, & König, 2018).…”
Section: Methodsmentioning
confidence: 69%
See 3 more Smart Citations
“…As in previous studies (Wahn et al, 2017; Wahn et al, 2020); our reasoning is that if dyads exceed this simulated joint performance, then they attained their higher joint performance by successfully collaborating in the tracking task (i.e., a division a labor division strategy). To differentiate this type of benefit from the collective benefit, and to denote that a collaboration between coactors is required, we henceforth refer to it as a “collaborative benefit” (for a more in-depth discussion of different types of group benefit criteria, see Wahn, Kingstone, & König, 2018).…”
Section: Methodsmentioning
confidence: 69%
“…Moving further along the information continuum (see Figure 1, second row), the next step is to identify when coactors transition from attaining group benefits without collaborating to attaining group benefits through collaboration. At this point, note that we generally assume that collaboration further enhances joint performance in joint visual tasks as several earlier studies found this to be the case (Brennan et al, 2008; Wahn et al, 2020; Wahn, Czeszumski, & König, 2018). Of course, as previously noted when investigations of joint motor control were reviewed, this is not necessarily true for all joint tasks (Knoblich & Jordan, 2003).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The second was that teams might have interacted in a way that improved their information sampling as they viewed the images. Most obvious was the possibility that searchers adopted a division-of-labor strategy (Malcolmson et al, 2007), either by making individual team members responsible for inspecting particular regions of the display, or alternatively, by making individual team members responsible for detecting particular targets (for evidence of similar strategies in speeded collaborative search, see Brennan, Chen, Dickinson, Neider, & Zelinsky, 2008;Niehorster, Cornelissen, Holmqvist, &Hooge, 2019 andWahn, Czeszumski, Labusch, Kingstone, &König, 2020; though see Yamani, Neider, Kramer, & McCarley, 2017, for evidence of increased overlap in oculomotor scanning in a team search, and McCarley, Leggett, & Enright, 2020, for behavioral evidence of inefficient team performance in a visual monitoring task).…”
Section: Introductionmentioning
confidence: 99%